HISTORY AND ASCENSION OF ANNATTO CULTIVATION IN THE MICROREGION OF DRACENA, SAO PAULO STATE - dos Santos, E. J.; Lourenzani, W. L.; Lourenzani, A. E. B. S. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Brazil is considered the world's largest producer of annatto. The crop is cultivated in different regions of the country. In the state of São Paulo, the Microregion of Dracena concentrates annatto production. The consumption of natural dyes is growing in the world due to risks to human health, caused by the use of artificial additives. This work aims at characterizing the development of annato cultivation in the Dracena Microregion. The choice for this object of analysis in this region, was due to the socioeconomic importance for the nation and state. The methodology was based on an exploratory qualitative study. Data collection involved a bibliographical review and a field study. We interviewed 15 annatto farmers in the region. Considering that this activity is characteristic of small production, and / or family farming, the maintenance and growth of the annatto productive system can favor regional development, contributing as an alternative to agricultural production, generating income and wellbeing for the rural population.